Tinjauan Hukum Terkait Kedudukan Calon Legislatif Mantan Tindak Pidana Korupsi Dalam Perspektif Hak Asasi Manusia - Choirunnisa Ariani; Kamila Nur Cahyani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Indonesia is a democratic state where the exercise of sovereignty is no longer directly entrusted to the people but to representatives of the people chosen through general elections. Here, all Indonesian citizens have the right to participate either as voters or candidates in legislative elections, including former corruption convicts. However, in practice, Regulation No. 20 of 2018 by the General Election Commission on the Nomination of Members of the People's Consultative Assembly, Regional Representative Council of the Province, and Regional Representative Council of the Regency/City limits the candidacy rights of former corruption convicts. Consequently, this General Election Commission Regulation contradicts the fundamental Human Rights principles upheld by Indonesian citizens. This research focuses on two aspects: examining and elucidating the legal status of former corruption convicts from the perspective of Human Rights and the legal regulations related to the legislative candidacy of former corruption convicts in General Election Commission Regulation Number 20 of 2018, viewed from the perspective of Human Rights. This research employs a normative juridical research method or doctrinal. The research findings indicate that former corruption convicts have the same legal status as ordinary citizens, namely equal standing in the eyes of the law. The Law No. 39 of 1999 on Human Rights and the 1945 Constitution protect the legal status of former convicts. Furthermore, the legal regulations regarding legislative candidacy for former corruption convicts in Article 4, paragraph (3) of General Election Commission Regulation No. 20 of 2018 are againts Human Rights. Especially in the Law on Human Rights, the 1945 Constitution, Constitutional Court Decisions, and Supreme Court Decisions.